Faces and Phases of Leadership: A Metaphoric Interpretation of Olusegun Obasanjo’s My Watch - OJO, Ayoola Sanmi; BAMGBOSE, Ganiu Abisoye (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This paper explores the deployment of conceptual metaphors in the memoir of former president Olusegun Obasanjo, examining how metaphorical affordances shape expressions and their purported meanings. Through a discourse analysis of the memoir, My Watch, the research shows how metaphors drawn from the second volume of the memoir create vivid description of the faces and phases of leadership through the author’s lens. The study relies on George Lakoff and Mark Johnson’s Conceptual Metaphor Theory. The paper discusses the faces and phases of leadership in volume two of former president Olusegun Obasanjo’s My Watch and explores the concepts of leadership. Seventeen excerpts are purposively selected and analysed based on their relevance to the discourse. Findings reveal that metaphors uncover servitude, reformation, fight, bliss, constant learning, healing and accomplishment inherent in leadership. All these show that the phases and faces of leadership are laced with changing conditions, internal demands, and outside influences. This study, therefore, posits that metaphors are engaged to show inherent semantics, and convey other messages to the reader. The findings of the research point to the role of the metaphors to better comprehend political memoirs and more importantly the intricacies of leadership.